INFLUENCE OF ESTRUS SYNCHRONIZATION PROTOCOLS ON FERTILITY PLASMA PROGESTERONE AND BIOCHEMICAL CONSTITUENTS IN KANKREJ COWS - BHORANIYA, B L; DHAMI, A J; KILLEDAR, ANKITA (The Indian Journal of Animal Reproduction, 2023)
The study was aimed to know the influence of different estrus synchronization protocols on plasmaprogesterone profile, certain biochemical constituents and fertility in 30 postpartum anoestrus Kankrej cows. Thestudy included use of Ovsynch, CIDR, Ovsynch plus CIDR and Heatsynch protocols on 24 anoestrus cows (6 ineach group) with blood sampling on day 0, 7, 9/11(AI) and on day 20 post-Al. One group each of 6anoestrus and6 normal cyclic cows was kept as untreated control and normal fertile control. There was 100 per cent estrusinduction response in all the treatment protocols. These animals were bred by fixed-time Al. Pregnancy wasconfirmed per rectum on day 60 post-Al. The conception rates at induced estrus in Ovsynch, CIDR, Ovsynch +CIDR and Heatsynch protocol were 33.33, 66.66, 50.00 and 16.67 per cent, respectively, as against 50.00 percent in normal cyclic group, while none of the anoestrus control animals expressed estrus till 32 days of follow-upperiod. The mean plasma progesterone concentrations were significantly higher on day 7 (5.727±1 .26, 4.37± 0.66,3.55±0.34 and 5.92±1.11 ng/ml, respectively) as compared to the corresponding values on day 0, 9/11 (Al) and onday 20 post-Al in all the 4 protocols. The overall mean plasma progesterone levels on the day of initiating treatmentwere low 'in all groups, rose following treatment and dropped to basal level on the day of induced estrus (Al) andagain rose significantly by day 20 post-Al in conceived as compared to non-conceived cows. Biochemicalinvestigations revealed that plasma total protein, total cholesterol, calcium and inorganic phosphorus levels werewithin normal physiological limits with overall means of 5.93±0.09 g/dl, 162.69±3.56 mg/di, 9,76±0.12 mg/di and5.11 ±0.14 mg/di, respectively. Their levels neither varied significantly between sampling days of different protocolsnor between protocols on any of the days/periods studied. The results showed that neither the reproductive status(cyclic/anoestrus) nor estrus synchronization protocols influenced the blood biochemical constituents studied,though they had significant effect on plasma progesterone profile and fertility of animals.
Keywords: Estrus synchronization protocols; Plasma progesterone; Metabolites; Kankrej cows